Discourse and identity: Unveiling the identity of Ping Fa Zhou in the Movie Mulan / Natasha Zuhaimi - Zuhaimi, Natasha (2023)
The above phrase is China’s portrayal of women during the ancient time. Just by reading the excerpt, it could be observed that women during the ancient China time were represented to be submissive and weak, to the extent that the role of women were not even significant. Unable to speak their own thoughts and do things as they please as if they are living in prison in their own body. Women during the ancient China time were molded by the philosophers and societies to follow the norm and culture brought by their ancestors. Cartwright (2018) stated that Confucius, one of many influential Chinese philosophers, believes that women should first be subservient to parents and then to husband, and also taught to be humble and only take the most menial duties. Confucius further stated that women should follow the Three Obedience and Four Virtues which are; obedience to father, to husband and to sons as widows; the virtues; morality, courteous speech, modest appearance and diligence. If they violate the Three Obedience and Four Virtues, they will be viewed as a disgrace to their family as well as a disgrace to the eyes of society. Likewise, the history of the famous Yin and Yang has also been depicted biased focusing the male as a strong entity.